PENGARUH ASIMETRI INFORMASI PADA SENJANGAN ANGGARAN DENGAN KECUKUPAN ANGGARAN DAN KETIDAKPASTIAN LINGKUNGAN SEBAGAI VARIABEL PEMODERASI - Pratiwi, Komang Arie; Widanaputra, A.A. G.P. (E-Jurnal Akuntansi; Vol 14 No 3 (2016), 2016)
The purpose of this study to determine the effect of information asymmetry on budgetary slack, with the adequacy of the budget and the uncertainty of the environment as moderating variables. The research was conducted at the regional work units (SKPD) in Tabanan regency. The population in this study were 43 SKPD and the number of samples studied were 129 peoples, using saturated sample, where the entire of population as research sample . Respondents were sampled in this study are head of department , Deputy. General and Planning, and head of sub-suction Financial department. Data collected through questionnaires. The analysis technique used is Moderate Regresion Analysis. Based on the analysis concluded that the adequacy of the budget and the uncertainty of the environment significantly moderate the influence of asymmetry of information on budgetary slack SKPD in Tabanan.
Keywords: information asymmetry, budgetary slack, the adequacy of the budget, the uncertainty of the environment.